Variability and Invariability in Fairy Tales (As the Example of the Translation of Grimms` Fairy Tales) - Dilafruz Halimovna, Karimova (International Journal of Psychosocial Rehabilitation, 2020)
The fairy-tale folklore is the oldest, popular, massively large-scale genre of both old and young. They originated in a very long time on the basis of mythological worldview, ancient customs and rituals of our primitive ancestors. In fairy tales, people's dreams about the everyday life and the most noble human qualities are often expressed through imaginary and life-long stories. Fairy tales have undergone a long process of formation as a genre. They are based on a simple story of primitive people.